Effect of Cooling Rate on the Longitudinal Modulus of Cu3Sn Phase of Ag-Sn-Cu Amalgam Alloy (Part I) - R. H. Rusli (Faculty of Dentistry, Universitas Indonesia, 2015)
Cu3Sn is indeed the ε phase in the Copper-Tin system, which is one of the main phase of High Copper Amalgam Alloy (Ag-Sn-Cu Alloy) and at present very little emphasis has been placed on the microstructure and the mechanical properties of Cu3Sn phase. In this study 3 castings of Cu-38.37 wt% Sn were produced. The casting specimens were subjected to different cooling rate conditions: as cast, air blown, and water quenched. The possible phases were identified by x-ray diffraction and the microstructure were examined on a metallurgy optical microscope. An ultrasonic equipment were utilized for longitudinal wave velocity measurements. Using this velocity the longitudinal modulus can be calculated. Phase identification on as cast, air blown and water quenched specimens indicated that the specimens consist of ε (Cu3Sn) phase. The smaller and finer microstructure of Cu3Sn phase was produced from water quenched (faster cooling rate) specimen. However its longitudinal modulus is significantly lower than the longitudinal modulus of as cast and air blown specimens. Therefore it is still need further investigation in order to obtain the transversal wave velocity and the Young's modulus.